Pengaruh Motivasi,Fasilitas Kerja Dan Kompetensi Terhadap Kinerja Pegawai Dinas Kependudukan Catatn Sipil Kabupaten Labuhanbatu Utara - Rambe, Siti Fatimah (Universitas Labuhanbatu, 2021)
This study aims to analyze the analysis of motivation, work facilities and competence to the performance of employees of the Department of population and civil registration of North labuhanbatu Regency. Data collection in this study was obtained through research instruments on a certain population / sample (quantitative approach) with a population as well as a sample of 35 employees. IBM SPSS sotwere 20.00 for windowes application is an application that is used in Data Processing (Data Testing ) in this study .the results showed that there is a positive and significant influence simultaneously between motivation, work facilities and competence on the performance of employees of the department and civil registry of North labuhanbatu Regency and also partially all all variables x affect the variable Y. Meanwhile, the coefficient of determinant R 2 obtained adjusted R squer value of 0.612 (61.2%). The rest (0.388%) on other variables that are not discussed in this study .